Induced Synthesis of Mycolactone Restores the Pathogenesis of Mycobacterium ulcerans In Vitro and In Vivo - Strong, Emily; Hart, Bryan; Wang, Jia; Orozco, Maria Gonzalez; Lee, Sunhee (Frontiers in Immunology, 2022)
Mycobacterium ulcerans is the causative agent of Buruli Ulcer (BU), the third most common mycobacterial infection. Virulent M. ulcerans secretes mycolactone, a polyketide toxin. Most observations of M. ulcerans infection are described as an extracellular milieu in the form of a necrotic ulcer. While some evidence exists of an intracellular lifecycle for M. ulcerans during infection, the exact role that mycolactone plays in this process is poorly understood. Many previous studies have relied upon the addition of purified mycolactone to cell culture systems to study its role in M. ulcerans pathogenesis and host response modulation. However, this sterile system drastically simplifies the M. ulcerans infection model and assumes mycolactone is the only relevant virulence factor expressed by M. ulcerans. Here we show that the addition of purified mycolactone to macrophages during M. ulcerans infection overcomes the bacterial activation of the mechanistic Target of Rapamycin (mTOR) signaling pathway that plays a substantial role in regulating different cellular processes, including autophagy and apoptosis. To further study the role of mycolactone during M. ulcerans infection, we have developed an inducible mycolactone expression system. Utilizing the mycolactone deficient Mul::Tn118 strain that contains a transposon insertion in the putative beta-ketoacyl transferase (mup045), we have successfully restored mycolactone production by expressing mup045 in a tetracycline-inducible vector system, which overcomes in-vitro growth defects associated with constitutive complementation. The inducible mycolactone expressing bacteria resulted in the establishment of infection in a murine footpad model of BU similar to that observed during the infection with wild-type M. ulcerans. This mycolactone inducible system will allow for further analysis of the roles and functions of mycolactone during M. ulcerans infection.